Influence of micro synthetic fibers confinement on properties of lightweight foamed concrete - Md Azree Othuman Mydin (Archives of Civil Engineering, 2022)
In this investigation, the confinement effects of micro synthetic fibers on lightweight foamed concrete (LFC) were examined. The parameters evaluated were porosity, water absorption, shrinkage, compressive strength, flexural strength and tensile strength. Three densities were cast which were 600 kg/m3, 1100 kg/m3, and 1600 kg/m3. Besides, the number of layers (1 to 3 layers) of micro synthetic fibers was also being examined. Based on the result obtained, the porosity improved by 8.0% to 16.3%, 13.8% to 25.6%, and 9.3% to 24.5% for the LFC with densities of 600 kg/m3, 1100 kg/m3, and 1600 kg/m3 confined with 1 layer, 2 layers, and 3 layers of micro synthetic fibers, respectively. Besides, for the water absorption test, the enhancements were 6.9% to 15.6%, 20.0 to 27.1%, and 12.2 to 29.6% for the respective densities and number of layers of micro synthetic fibers employed, while the drying shrinkage improved by 48.5% to 76.8%, 57.4% to 72.1%, and 43.2 % to 68.2% for the respective densities and number of layers of micro synthetic fibers employed. For the strength properties, a confinement with 3 layers of micro synthetic fibers showed significant results, where enhancements of 153% (600 kg/m3), 97% (1100 kg/m3), and 102% (1600 kg/m3) were obtained for the compression strength; 372% (600 kg/m3), 258% (1100 kg/m3), and 332% (1600 kg/m3) for the bending strength; and 507% (600 kg/m3), 343% (1100 kg/m3), and 332% (1600 kg/m3) for the splitting tensile strength, respectively, compared to the control LFC.